Cardiac Magnetic Resonance T1-Mapping of the Myocardium: Technical Background and Clinical Relevance. Issue 2 (March 2018) - Muscogiuri, Giuseppe; Suranyi, Pal; Schoepf, U. Joseph; De Cecco, Carlo N.; Secinaro, Aurelio; Wichmann, Julian L.; Fuller, Stephen R.; Lesslie, Virginia W.; Varga-Szemes, Akos
Abstract : Myocardial T1-mapping has become feasible over the past decade as emerging technological magnetic resonance imaging advances enable increasingly rapid and reliable acquisition techniques. A variety of T1-mapping sequences are in development, with most allowing for the acquisition of a single-slice T1-map in a single breath-hold. The development of these protocols has spurred investigation into a wide range of potential clinical uses, including the characterization of cardiomyopathies. Although native T1-mapping provides superior tissue characterization, postcontrast T1-mapping is still indispensable for extracellular volume quantification. Ongoing and future studies should investigate the reliability, reproducibility, accuracy, and precision of available techniques and establish disease-specific reference values for T1-mapping-based parameters.